Regulatory sequences involved in the translation of Neurospora crassa mRNA: Kozak sequences and stop codons - J. J. P. Bruchez; J. Eberle; V. E .A. Russo (Fungal Genetics Reports, 1993)
We have analyzed the sequences of 77 nuclear genes of N. crassa thought to be transcribed by RNA polymerase II (References 1-72) which should represent virtually all of the presently published nuclear gene sequences for this fungus.